Manfaat Ekonomi dan Daya Dukung Wisata di Kawasan Geopark Nasional Ciletuh-Palabuhanratu Kabupaten Sukabumi - Saputro, Widhi Depi; Ekayani, Meti; Thamrin, Fifi Diana (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2025)
ABSTRACT The activity of geotourism in the region Ciletuh-Palabuhanratu National Geopark (GNCP) shows an increase in the number of tourists visit post was designated as a national geopark. An increasing number of tourists visit the positive impact to the local economy, but on the other hand could potentially pose a negative impact to the environment. Positive impact in the form of economic benefits with the additional income for the tourist trade and local labor absorption. How big is the value of the economic benefits envisaged from the value of the share and covering, where the perpetrators of the attempt at gaining share Amphiteater Panenjoan of 76.44% and covering of 130.24%, whereas in Curug Sodong share of 96.39% and covering of 116.06%. On the other hand, the increasing number of tourists visit potentially pose a negative impact to the environment. Based on the analysis of carrying capacity by the method of Cifuentes, on the level of the physical carrying capacity (PCC), the number of tourist visits at the time of peak-season generally already exceed the capacity of the resource support. The same condition occurs at the level of real carrying capacity (RCC) which shows has happened over carrying capacity. Keyword: Ciletuh Geopark, economic benefits, geotourism, tourism carrying capacity